Promotion Strategy through Live Shopping in Increasing Sales Volume of Bykiddos Sidoarjo - Maharani, Liany Fari Adelia; Kusumasari, Indah Respati (Formosa Journal of Multidisciplinary Research, 2024)
Various forms of electronic transactions known as e-commerce include individual online stores, sales websites, and other electronic trading platforms. Shopee is now one of the most popular marketplaces in Indonesia. Shopee has updated its services with the Shopee Live feature. Bykiddos is one of the sellers offering its products through the Shopee platform. Although the revenue from sales on Shopee Live varies, its turnover is quite high. Therefore, Bykiddos must continue to strive to develop its business by using the right promotional strategies, especially with the Shopee Live feature. The purpose of this research is to understand and analyze promotional strategies through live shopping in relation to sales volume on the Shopee account Bykiddos. This research adopts a qualitative descriptive approach. The researcher chose this approach to analyze the live shopping promotion strategies in enhancing the online sales of Bykiddos through SWOT analysis, which requires good interview skills and a deep understanding of the social context. This study shows that the implementation of promotional strategies through the live shopping feature on Shopee has been well managed. Based on the SWOT analysis, Bykiddos is positioned in quadrant I with the values (X;Y) (1.43;1.25), indicating that an aggressive strategy needs to be implemented  to  leverage  strengths  in  seizing available opportunities.